Genome-Wide Association Study-Guided Exome Rare Variant Burden Analysis Identifies IL1R1 and CD3E as Potential Autoimmunity Risk Genes for Celiac Disease - Mansour, Haifa; Banaganapalli, Babajan; Nasser, Khalidah Khalid; Al-Aama, Jumana Yousuf; Shaik, Noor Ahmad; Saadah, Omar Ibrahim; Elango, Ramu (Frontiers in Pediatrics, 2022)
Celiac disease (CeD) is a multifactorial autoimmune enteropathy characterized by over-activation of the immune system in response to dietary gluten. The molecular etiology of CeD is still not well understood. Therefore, this study aims to identify potential candidate genes involved in CeD pathogenesis by applying multi-layered system biology approaches. Initially, we identified rare coding variants shared between the affected siblings in two rare Arab CeD families by whole exome sequencing (WES). Then we used STRING database to construct protein network of rare variants and genome wide association study (GWAS) loci to explore their molecular interactions in CeD. Furthermore, the hub genes identified based on network topology parameters were subjected to a series of computational validation analyses like pathway enrichment, gene expression, knockout mouse model, and variant pathogenicity predictions. Our findings have shown the absence of rare variants showing classical Mendelian inheritance in both families. However, interactome analysis of rare WES variants and GWAS loci has identified a total of 11 hub genes. The multidimensional computational analysis of hub genes has prioritized IL1R1 for family A and CD3E for family B as potential genes. These genes were found to be connected to celiac disease pathogenesis pathways such as T cell selection, cytokines signaling, and adaptive immune response pathways. Future multi-omics studies may uncover the roles of IL1R1 and CD3E in gluten sensitivity. The present investigation lays forth a novel approach integrating next generation sequencing (NGS) of familial cases, GWAS, and computational analysis for solving the complex genetic architecture of CeD.